ANALISIS TEKSTUR DAN VISKOSITAS BAHAN PENGENTAL LOKAL SEBAGAI PENGGANTI FOOD THICKENER KOMERSIAL UNTUK PASIEN GANGGUAN MENELAN - Guritno Adistyawan; Pratiwi Dinia Sari; Leiyla Elvizahro; Aprillia Dewi Arum Nur P (Academic Hospital Journal, 2021)
ABSTRACT  Background: Management of cases of difficulty swallowing in Indonesia has so far only used standardized forms of hospital food consisting of ordinary foods, soft foods, chopped foods, filtered foods and liquid foods. In developed countries, the use of commercial food thickener is commonly used for cases of swallowing disorders. Commercial food thickener products are difficult to obtain in Indonesia and the price is quite expensive so that substitute products that are derived from local and cheap food are needed.It is necessary to develop an alternative formulation of food thickener made from local which is easily obtained and cheaper in price as an alternative solution to the problem of eating difficulties. Some ingredients that have properties as a food thickener are glucomannan porang and xanthan gum. Porang glucomannan has a high fiber content while xanthan gum has high viscosity in low concentration. Objective: The purpose of this study was to determine the texture and viscosity of local thickener food in accordance with the consistency of commercial food thickener as a gold standard. Design: eksperimental laboratorium research which is held at the Nutrition Department in UGM Academic Hospital on June until November 2019, with the research steps are: 1) Make a standard gold solution of 6 grams of commercial food thickener 2) Measuring the texture and viscosity of a standard gold solution used as a comparison with other products 3) Conducting subjective and objective tests of local ingredients, namely glucomannan porang and xanthan gum. Results: From the research conducted in the laboratory by using the RVA method, all 4 flour (cornstarch, sago flour, arrowroot flour, tapioca flour and porang glucomannan flour) showed a viscosity close to the thickness of commercial food thickener. The advantage of glukomanan flour is that after the maximum viscosity value is reached, the viscosity does not change with an increase in temperature or when the temperature decreases. Conclusions: Porang glucomannan has a texture similar to commercial food thickener (gold standard), the viscosity of porang glucomannan tends to be stable with changes in temperature and when the temperature decreases so that it can be used as an alternative food thickener for dysphagia patients.